2023
DOI: 10.1111/1477-8947.12312
|View full text |Cite
|
Sign up to set email alerts
|

The asymmetric impact of fossil fuel and renewable energy consumption on life expectancy in Nigeria

Abstract: The life expectancy rate is an essential yardstick for measuring people's well–being. The healthier the population, the better the economic rate of productivity. Not many studies have investigated the asymmetric link between energy use and life expectancy. Thus, this paper addresses the gap by evaluating the impact of fossil fuel (FFEC) and renewable energy consumption (RNEW) on life expectancy (LEXP) in Nigeria from 1965–2019 using the Autoregressive Distributed Lag (ARDL) and Non‐linear ARDL methods. The bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…A better future is possible because education equips individuals with knowledge of healthy living, disease prevention, and expanded business opportunities [12]. Both the immediate and distant futures are profoundly impacted by the use of renewable energy sources in proximity to petroleum derivatives [13]. In general, it could be worth it to trade an additional year in the future for about 9% of annual customer expenditure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A better future is possible because education equips individuals with knowledge of healthy living, disease prevention, and expanded business opportunities [12]. Both the immediate and distant futures are profoundly impacted by the use of renewable energy sources in proximity to petroleum derivatives [13]. In general, it could be worth it to trade an additional year in the future for about 9% of annual customer expenditure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, Somoye et al (2023) used the linear and nonlinear ARDL methods and concluded that fossil fuel consumption enhances life expectancy in Nigeria. Warsame (2023) applied the Kernel regularised least squares (KRLS) procedure and deduced that ecological pollution has an insignificant effect on life expectancy in Somalia.…”
Section: The Ecological Burden-qol Associationmentioning
confidence: 99%